Bridging the Blue - Smolic, Aljosa (Carnegie Mellon University, Pittsburgh: ETC Press, 2020,, 2020)
Bridging the Blue is an attempt to harness tech-nology as an enabler of empathy through using its qualities and possibilities to challenge how we listen. Feedback to date suggests that Bridging the the Blue offers an evaluative space for listening and the potential to consider empathic listening through an innovative and immersive experience. In particular, making use of novel technology and the attributes allowing for the viewer’s experienced and embodied encounter with the work, limited agency and 'making strange' to offer effective ways of listening, and making it safer for those who are struggling to end their silence and reduce the stigma around negative mental health.
The Art Exhibit at ICIDS 2019 Art Book: The Expression of Emotion in Humans and Technology,
PUBLISHED
Pittsburgh
Keywords: Creative Arts Practice; Creative Technologies; Inclusive Society; Multimedia & Creativity; Mental Health/Psychosocial disability; Other